Penerapan Model Protokol AAA (Authentication, Authorization, Accounting) Pada Pengamanan Jaringan Komunikasi WAN (Wide Area Network) - Sembiring, Abdul (Cattleya Darmaya Fortuna, 2020)
Security is the most important aspect in a computer network. Both in networks that are local or not. The main problems that are often found on computer networks include the destruction of system devices, access to information, changes in information and deletion of information by people who do not have the right to that information. The development of technology for now, almost all agencies have used computer networks such as WAN where the function can connect LAN networks in a large geographical area and be able to exchange data packets and frames between routers and switches. The AAA protocol model (Authentication, Authorization, Accounting) can be used one at a time or combined as needed. Using this network model will be far safer than using only one security process. This model can be processed by the necessary networks and results in effective communication. This model also divides these processes into logical groups called layers.